Dinosaur search - Waring, Rob.; Waring, Rob. (Boston : Thomson Heinle, 2008)
'Dinosaurs' are animals that lived long ago. Scientists often study dinosaur 'bones,' or the hard parts inside the body. A team of scientists is looking for dinosaur parts but they're hard to find. Will the team find bones, or something else?
1 2
Keywords: Readers; Dinosaurs -- Juvenile literature; Paleontology -- Africa,North -- Juvenile literature